CgVeA, a light signaling responsive regulator, is involved in regulation of chaetoglobosin A biosynthesis and conidia development in Chaetomium globosum - Zhengran Wang; Shanshan Zhao; Kai Zhang; Congyu Lin; Xin Ru; Qian Yang (Synthetic and Systems Biotechnology, 2022)
Cytochalasans, with diverse structures and pharmacological activities, are a class of compounds containing isoindolinone moieties fused to the tricyclic or tetracyclic ring system. Chaetoglobosin A (cheA), mainly produced by Chaetomium globosum, is the most abundant cytochalasan. However, limited understanding of transcriptional regulation of morphological development and cheA biosynthesis in C. globosum has hindered cheA application in agriculture and biomedical field. This study examined the regulatory role of CgVeA gene in C. globosum. CgVeA had significant effect on secondary metabolites production in C. globosum, similar to that reported in other filamentous fungi. Inactivation of CgVeA caused an obvious decrease in cheA production from 51.32 to 19.76 mg/L under dark conditions. In contrast, CgVeA overexpression resulted in a dramatic increase in cheA production, reaching 206.59 mg/L under light conditions, which was higher than that noted under dark condition. The RT-qPCR results confirmed that CgVeA, as a light responsive regulator, positively regulated cheA biosynthesis by controlling the expression of core genes of the cheA biosynthetic gene cluster and other relevant regulators. Electrophoretic mobility shift assays proved that CgVeA directly regulated LaeA, cheR, and p450, and indirectly regulated PKS. Moreover, CgVeA had a significant effect on the regulation of asexual spores production. When compared with wild-type C. globosum, CgVeA-silenced and CgVeA overexpression mutants presented remarkable differences in sporulation, irrespective of light or dark condition. Besides, CgVeA expression was speculated to negatively regulate spore formation. These findings illustrated the regulatory mechanism of a hypothetical global regulator, CgVeA, in C. globosum, suggesting its potential application in industrial-scale cheA biosynthesis.